Art without waste 500 upcycled and earth-friendly designs - Wongpakdee, Patty K. (Rockport Publishers, 2014)
"Art without waste showcases a collection of creative reuse and re-imagination of everyday items such as clothing, handbags, furniture, housewares, and even art itself. Each item featured within was designed using existing materials through clever manipulation to create one-of-a-kind treasures--dresses made from t-shirts and cut-up jeans; jewelry made from rocks, buttons, measuring tape, and scalp metal; furniture made from bike tires,wine corks, car parts, and tennis balls. Packed with inspiration and ideas, you can create your own recycled art objects with a little muster and ingenuity. So dig in, get motivated, and create giving disposable items new life while contributing to the earth's sustainability"--Provided by publisher.